Factors affecting Malaysian ESL teachers' behavioral intentions for technology use in the post-COVID-19 era - Chun, Teo Woon; Yunus, Melor Md (Frontiers in Psychology, 2023)
This study aimed to investigate ESL teachers’ technology acceptance level and factors affecting their behavioural intention (BI) towards technology use in post-COVID-19 settings. A cross-sectional survey that involved 361 Malaysian ESL teachers was conducted. They were recruited via convenience sampling method, and they answered an online survey questionnaire which was devised with the reference to past studies. The collected data was analysed via descriptive, Pearson’s correlation and multiple regression analyses. The findings depicted that Malaysian ESL teachers generally held a high level of technology acceptance level in post-COVID-19 era. Their BI had a significant relationship with three factors, namely performance expectancy (PE), effort expectancy (EE) and social influence (SI), in which EE was identified as the most significant factor that influenced their BI towards technology use in post-COVID-19 era. Conversely, ESL teachers’ facilitating conditions did not have a substantial connection with their behavioural intention towards technology use after the pandemic, despite that they had a weak positive relationship with each other. This study provided an insight to the field of educational psychology by identifying the current trends on ESL teachers’ behavioural intention in adopting technology at post-COVID-19 ESL classroom. The findings of this study also provided support for investigations into technology acceptance in teaching of ESL, illustrating a growing need to include adequate educational technological tools, resources, and facilities to facilitate ESL teachers’ lesson delivery. Future studies are recommended to conduct longitudinal research and investigate more variables from different technology acceptance models.